Wearing compression garment enhances central hemodynamics? A systematic review and meta-analysis - Lee, D. C.; Ali, A.; Sheridan, S.; Chan, D. K.; Wong, S. H. (The Journal of Strength and Conditioning Research, 2022)
Compression garments (CG) are believed to enhance exercise performance and recovery by improving central hemodynamic responses. However, evidence is inconclusive. We performed a systematic review and meta-analysis to determine the effect of wearing CG at rest or after a physiological challenge on central hemodynamic responses, including cardiac output, stroke volume (SV), heart rate (HR), systolic blood pressure, diastolic blood pressure (DBP), and systemic vascular resistance in healthy individuals. The English language searches of the electronic databases SPORTDiscus, MEDLINE, and Web of Science were conducted from November 2018-February 2019. The studies involved were limited to the following: (a) original articles; (b) randomized controlled trials; (c) monitoring of central hemodynamic responses (either at rest or after a physiological challenge: maximal exercise or orthostatic challenge); and (d) healthy individuals. Of the 786 studies identified, 12 were included in the systematic review and meta-analysis. Meta-analysis was performed by the restricted maximum likelihood method. The results indicated that the effect size (ES) of wearing CG on improving central hemodynamic responses was large overall (Hedges' g = 0.55) and was large in SV (Hedges' g = 1.09) and HR (Hedges' g = 0.65). Subgroup analysis showed that the ESs in "post-physiological challenge" was large in overall (Hedges' g = 0.98), SV (Hedges' g = 1.78), HR (Hedges' g = 1.10), and DBP (Hedges' g = 0.75). Their ESs in "at rest" were not significant in all central hemodynamic responses, apart from a significant medium ES observed in SV (Hedges' g = 0.44). Healthy individuals who wear CG have marked improvement in central hemodynamic responses, particularly after a physiological challenge. More pronounced effects of CG are observed in increasing SV and reducing HR.